Survey of sensory attributes of skimmed and whole milk gourmet brigadeiros by men and women (Research, Society and Development, 2020)
The female sex has a greater search for sweets, this can be affected by several factors, in this research follow-up the present work aimed to survey and compare sensory attributes of gourmet brigadeiros produced with skimmed and whole milk condensed milk among male tasters and female. For the formulation of gourmet brigadeiros, skimmed and whole milk condensed milk and cocoa powder were used, so the gourmet brigadeiros were elaborated through the aid of the microwave oven, where the cooking process that takes place by means of electromagnetic waves lasted 5 minutes. In the first sensory analysis attributes (network method) were raised based on the quantitative descriptive analysis of (CATA Check-All-That-Apply) and aimed to raise attributes among the sensory profiles of appearance, aroma, flavor and texture, followed by the second sensory analysis, the continuation being the Quantitative Descriptive Analysis, in which a form with the attributes most commented by the tasters was given. The sensory analysis data were computed by the computer program R. using Cochran's Q tests and correspondence analysis. For the Cochran Q test, the p-value at 5% significance was stipulated, which provided the results of only four significant attributes and the graph of the correspondence analysis that allowed the view on the male sex to stand out more than the female sex. Thus, only four attributes showed a difference, which are appearance (soft), aroma (acid), flavor (acid) and texture (hard) and when comparing the gourmet brigadeiros of whole milk consumed by tasters of both sexes and gourmet brigadeiro of skimmed milk consumed by tasters of both sexes, it was found that there is greater dispersion of men with greater variability in the perception of attributes.